Welfare states in transition. East and West (London, 1999)
"Social policy in East and West finds itself today in the middle of a fundamental transition. The former communist countries of Central and Eastern Europe and the successor states to the former Soviet Union are attempting to create the institutions needed for a modern market economy and a modern democratic welfare state. At the same time, the mature welfare states of Europe are struggling to solve the contemporary financial crisis of their systems of social entitlements. Because of fundamental economic and demographic trends, these systems will become increasingly difficult to sustain over the coming decades. This volume represents the initial results of a trilateral research cooperation of the University of Pittsburgh (Centre for International Studies), the Charles University of Prague and the Free University Berlin. In addition to participants from the three partner institutions, other distinguished scholars from Europe and the United States were invited to the symposium held at the Free University Berlin from which the present volume results. The contributors overwhelmingly agree that it would be mistaken policy for the eastern economies in transition to simply copy the institutions of western welfare states. Instead one can learn much from the experience gathered over the past half-century in western welfare states. This is especially true with respect to the long-run sustainability of important institutions of social policy. Learning from this experience, social policymakers in the West have an obligation not to repeat their own past mistakes. This interdisciplinary critical examination of the social policy transitions in East and West will provide valuable assistance."